Low Plasma Potassium and High Iron Levels Increased the Risk of Dyslipidemia among Non-Diabetic Taxi-Motorbike Drivers Living and Working in Cotonou, Benin - AVOGBE, PATRICE HODONOU; SANNI, AMBALIOU (My University, 2022)
Non-traditional cardiovascular risk factors such as iron and potassium may play a role in lipid metabolism. However, information on this association is lacking in populations of Benin. This study evaluated the associations be- tween plasma iron and potassium levels and risk of dyslipidemia among taxi- motorbike drivers (TMDs) in Cotonou. We conducted a cross-sectional study on 134 males TMDs aged ≥20 years old, of whom 39 (29.1%) had dyslipide- mia. Plasma biochemistry including measurements of total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high- density lipoprotein cholesterol (HDL-C), iron, and potassium were performed. Dyslipidemia was defined as any or combinations of the following: TC > 5.2 mmol/L, LDL-C > 3.4 mmol/L, TG > 1.7 mmol/L, and HDL-C < 0.9 mmol/L. Participants were segregated into tertiles based on plasma iron and potassium levels. The associations of plasma iron and potassium levels with dyslipidemia were evaluated through multivariate logistic regression to calculate the odd ratios (ORs) and 95% confidence intervals (CIs). Logistic regression showed that plasma iron level was independently and positively correlated with the risk of dyslipidemia, in a dose-dependent manner. The OR for developing dyslipidemia comparing the 3rd tertile (>18.8 μmol/L) to the 1st tertile of plasma iron (<13.6 μmol/L) was 3.85, (95% CI: 1.20 - 12.35, p = 0.023). We observed similar patterns of association in a subgroup analysis restricted to normoten- sive patients, although the estimates lacked statistical significance. Our findings also revealed that the risk of dyslipidemia decreased when plasma potassium levels increased. The OR (95% CI) for dyslipidemia comparing the 2nd tertile (4.4 - 4.8 μmol/L) to the 1st tertile (<4.3 μmol/L) of potassium was 0.31 (0.11 - 0.86, p = 0.025). Interestingly, the risk of dyslipidemia decreased progressively (81% to 86%) and significantly across plasma potassium tertiles when restricting analysis to normotensive patients. The ORs (95% CI) for dyslipidemia comparing the 2nd and 3rd tertiles to the 1st tertile of plasma po- tassium were 0.19 (0.04 - 0.87, p = 0.032) and 0.14 (0.02 - 0.93, p = 0.043). In conclusion, our study shows that higher plasma iron and low potassium le- vels are significant predictors of dyslipidemia in TMDs. As such, the find- ings have public health implications for predicting and preventing dyslipide- mia and associated cardiometabolic diseases. However, longitudinal studies are needed to determine if disturbances in iron and potassium levels, even within the normal range, are precursors or consequences of dyslipidemia.
Keywords: Cotonou; Dyslipidemia; Iron; Potassium; Taxi-Motorbike Drivers